2015
DOI: 10.1016/j.jped.2015.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Circulating endothelial progenitor cells in obese children and adolescents

Abstract: Circulating endothelial progenitor cell count is elevated in obese children and adolescents with evidence of endothelial activation, suggesting that, during infancy, endothelial repairing mechanisms are present in the context of endothelial activation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…22 Similarly, endothelial progenitor cells, which are bone marrow-derived progenitor cells involved in neovasculogenesis and maintenance of vascular integrity, 43 are increased in obese youth. 44,45 While this suggests early endothelial damage, it also shows that the adaptive response to the haemodynamic consequences of obesity and the endothelial reparative mechanisms are still well intact among obese children, suggesting that early intervention to revert obesity during childhood may revert also their cardiovascular risk. factors that should be considered.…”
Section: Vascular Changesmentioning
confidence: 99%
“…22 Similarly, endothelial progenitor cells, which are bone marrow-derived progenitor cells involved in neovasculogenesis and maintenance of vascular integrity, 43 are increased in obese youth. 44,45 While this suggests early endothelial damage, it also shows that the adaptive response to the haemodynamic consequences of obesity and the endothelial reparative mechanisms are still well intact among obese children, suggesting that early intervention to revert obesity during childhood may revert also their cardiovascular risk. factors that should be considered.…”
Section: Vascular Changesmentioning
confidence: 99%
“…Similarly, endothelial dysfunction has been demonstrated in obese children [ 17 , 18 ]. In these children, compensatory elevation of circulating endothelial progenitor cell counts suggest that in early life, obesity-mediated endothelial dysfunction may still be reversible [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that most metabolically healthy obese individuals do not exhibit a high risk of diabetes development where IR is present (40). In addition, the numbers of angiogenic progenitor mononuclear cells appear to be increased in the MetS patient population (41). In contrast, MetS individuals have shown decreased levels of progenitor mononuclear cells with angiogenic immune phenotypes (42), which independently predict CV and atherosclerotic disease progression (43,44).…”
Section: Discussionmentioning
confidence: 99%